Designing Promotional Media for Nasi Jamblang Ibad Otoy - Herdianto, Tedi; Anggraeni, Shafa Puteri (Eduvest - Journal of Universal Studies, 2023)
Digital promotion is very influential in product marketing, especially in this digital era, many companies implement digital promotions through their social media accounts to reach a wider target audience. This is also used by Nasi Jamblang Ibad Otoy in marketing products in Indonesia. However, in carrying out digital promotions, the company experiences various obstacles in creating promotional content on Instagram. In designing promotional media from the Nasi Jamblang Ibad Otoy product, the study aims to apply marketing efforts by creating advertisements in the form of Instagram content using the Integrated Marketing Communications (IMC) method which contains SWOT data analysis by sorting out in terms of strengths, weaknesses, opportunities, and threats that exist in the company. Then the author analyzes the Unique Selling Proposition (USP) of the company. This design produces promotional media in the form of Instagram feed content, Instagram stories, and supporting media in the form of merchandise from Nasi Jamblang Ibad Otoy. It is hoped that the design of promotional media on Instagram can attract customers from Cirebon outside the city to buy products, so that the company's income can reach the target.